(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
From a linguistic typology perspective, some clarifications are offered to the debate on possible Iberian numerals. First, to determine whether these forms can be considered numerals, and second, whether their origin is due to borrowing or genetic relationship. For the first question, the proposal by Orduña and Ferrer i Jané is summarized, drawing on research on linguistic universals and numerals, as well as on cognitive linguistic studies by Hurford. For the second question, The World Loanword Database is reviewed, focusing on instances of borrowing in numeral systems. An in-depth analysis is conducted on three languages from the sample, and the circumstances in which the phenomenon occurs are extrapolated. The findings suggest a higher probability of borrowing than previously expected, although under specific conditions.